Block allotransplantation of both lungs with pulmonary trunk and left atrium in dogs. Issue 4 (July 1972) - Vanderhoeft, P.; Dubois, A.; Lauvau, N.; de Francquen, Ph.; Carpentier, Y.; Rocmans, P.; Nelson, R.; Kaufman, S.; Brickman, L.; Gyhra, A.; Ectors, P.
Abstract : Eleven dogs received a double-lung-block allotransplantation under cardiopulmonary bypass. Six dogs survived over one hour with spontaneous breathing and normal right ventricular pressures. Postoperative blood gases and pressures are given for six animals. These data show a fall in systemic blood pressure and arterial oxygen partial pressure, a rise in PCO 2, and no change in pH after completion of transplantation. Causes of death were haemorrhage (7), inadequate cardiopulmonary bypass (2), early anoxic heart lesion (1), and post-perfusion low output syndrome (1).